Determination of Priority Poly Aromatic Hydrocarbons Using Solid Phase Extractionand HPLC in Diyala River - Jasim, Hadi Hassan; Sultan, Muntadhar Salih (Al-Nahrain Journal of Science, 2018)
In this paper sixteen polycyclic Aromatic Hydrocarbons (PAHs) were estimated in eight sites along Diyala River where entering Baghdad province until flows into Tigris River, (PAHs) organic compound dscontain two or more fused rings. Some of these compounds are classified as carcinogenic and mutagenic pollutants. Solid Phase extraction was used in this work to concentrate PAHs in water samples using Sep-back C18 showed percentage recoveries between (82-97) percent. High Performance Liquid Chromatography (HPLC) with UV-Vis detector was used for determination of PAHs. The result of PAHs concentrations were found in the water samples range between (zero -186.86)ng/ml. According to our results sites number one, two, six, seven and eight have the least values of total PAHs concentration with 10.8, 12.0, 39.3, 30.7 and 14.9 ng/ml respectively, while, three, four and five sites have a largepolluted with 396.5, 660.9 and 189.5 ng/ml respectivelybecause these sites are near pollutants sources. Naphthalene, Anthracene and Fluoranthene with total concentrations415.8, 259.2 and 286.4 ng/ml respectively, compounds Benzo [a] pyrene and Dibenz [a, h] anthracene arenot detected in all sites.Keywords:poly aromatic hydrocarbons (PAH),High performance liquid Chromatography (HPLC),Solid Phase Extraction (SPE),Diyala River